Impact of vaccine wastage rate on national vaccine management and immunization schedule: A case study of DTP, DTP-HB and DTP-HB-Hib vaccine - Yoocharoen, Pornsak; Chuanark, Piyanart; Ut-ang, Kattiya; Rattanayot, Jarawee (Disease Control Journal, 2021)
Vaccine is a crucial tool in public health intervention to prevent and protect against the vaccine preventable diseases (VPDs). An efficient vaccine management should be considered based on cost-benefit assessments for the general population. The vaccine wastage is a key factor to manage and balance between cost and benefit for the national immunization program (also known as the EPI program). The objective of this study is to determine the ways and factors that can reduce a wastage rate on the EPI program. A descriptive cross-sectional study was conducted by multi-stage simple random sampling on participating health facilities at all levels. A total of 242 health facilities were selected from 12 districts of 12 sampling provinces. A total of 2,945 vaccine request forms (V.3/1) were analyzed. A mean vaccine wastage rate of DTP-HB and DTP was 36.07 and 45.19, respectively. The wastage rate was higher than expected national target, i.e. not greater than 25% for 10 doses/vial of vaccine package. It was found that 18.7% of wastage rate was caused by less than five children coming to receive the vaccine, and 49.4% of wastage rate was due to less than 10 children visit a health facility for vaccination. Based on the findings, a lower number of children is the main cause of high vaccine wastage rate that appeared to be unavoidable. When the size of vaccine package had been changed to 5 and 2 doses/vial, the wastage rate was reduced to 18.03% and 6.12%, respectively. On the other hand, to increase a dose or doses of vaccine for the immunization schedule to 4 and 5 doses of DTP-HB, wastage rate was found to have decreased to 25.96% and 20.75%, respectively. At present, the EPI program has replaced DTP-HB with DTP-HB-Hib to prevent meningitis and pneumonitis from Hib. Conclusion: For an effective vaccine management to reduce the vaccine wastage rate and improve a cost-benefit ratio to prevent the diseases, the national immunization schedule should implement a change in DTP-HB-Hib package from 3 doses to 4 or 5 doses or, alternatively, replace DTP vaccine with DTP-HB-Hib as a single formular vaccine. This change will need an additional budget of approximately 7-13 million Baht/year, representing 0.87-1.0% of total budget, for a new immunization schedule to increase immunity and improve service delivery and safety for the EPI program.